Botrylloides pizoni, a new species of Botryllinae (Ascidiacea) from the Mediterranean Sea R. - Brunetti, R.; Mastrototaro, F. (Zootaxa, 2012)
A new ascidian species belonging to the Botryllinae was discovered in the Gulf of Taranto (South Italy). This new species wascollected in different seasons over a period of several years, which allowed information about its biology to be obtained. Thenew species presents large zooids arranged in ladder systems. The zooids have several rows of stigmata, the second one com-plete, ovary posterior to testis, one larva per side developing in an incubatory pouch, and a peculiar arrangement of the gut loop. The new species is named Botrylloides pizoni after the great French zoologist Antoine Pizon (1860–1942).